INTEGRATED MOLECULAR DOCKING AND ADMET ANALYSIS OF Hyoscyamus niger METABOLITES TARGETING Α-GLUCOSIDASE AND Α-AMYLASE FOR ANTIDIABETIC THERAPY - Paz, Cristian; Iqbal , Muhammad Javid; Burgos, Viviana; Villegas, Cecilia; Iqbal, Sana (Journal of the Chilean Chemical Society, 2025)
The global diabetes epidemic requires safer therapeutic alternatives to conventional α-glucosidase and α-amylase inhibitors, which cause significant gastrointestinal side effects. Natural products provide structurally diverse scaffolds for antidiabetic drug discovery. This study evaluated the dual enzyme inhibitory potential of Hyoscyamus niger L. (black henbane) through integrated experimental and computational approaches. Methanolic extracts of H. niger seeds were assessed for α-glucosidase and α-amylase inhibitory activities using enzymatic assays. H. niger extract exhibited superior inhibitory activity compared to acarbose, with IC₅₀ values of 35.85 ± 5 μg/mL (α-glucosidase) and 44.56 ± 5 μg/mL (α-amylase) versus acarbose’s IC₅₀ values of 141.0 ± 5 μg/mL and 131.0 ± 10 μg/mL, respectively. 100 phytochemicals were subjected to molecular docking against target enzymes (PDB IDs: 3L4Y and 3BAJ). Lead compounds were evaluated for drug-likeness using Lipinski’s Rule of Five and comprehensive ADMET profiling. Molecular docking identified one coumarinolignan called cleomiscosin B as the most promising lead compound, demonstrating excellent binding affinities (-8.1 kcal/mol for both enzymes), complete Lipinski compliance, and favorable safety profiles with no AMES toxicity. In spite to pongamoside D was also founded as the top dual-target inhibitor with binding affinities of -9.3 kcal/mol (α-amylase) and -8.3 kcal/mol (α-glucosidase). However, ADMET analysis suggested that pongamoside D violated Lipinski’s rule and showed positive AMES toxicity with possible carcinogenicity risk. This study establishes H. niger as a valuable source of novel dual-target antidiabetic compounds, with cleomiscosin B representing a promising alternative to synthetic inhibitors.